Myeloid differentiation factor 88 expression in eyelid specimens of rosacea. (4th May 2022) - Wladis, Edward J.; Arunachalam, Thilaka; LaJoie, Juliann E.; Lau, Kevin W.; Adam, Alejandro P.
ABSTRACT: Purpose: Rosacea is a common cause of ocular surface disease. Specific immunologic features have been implicated in its pathogenesis, including toll-like receptors, mitogen-associated kinase, and nuclear factor kappa-B. Myeolid differentiation factor 88 (MYD88) has been associated with these elements, suggesting a role for this protein in rosacea. This study was designed to compare the expression of MYD88 in the eyelids of patients with and without this disease. Methods: Western blotting for MYD88 was performed in 14 control patients and 15 patients with rosacea. Bands were quantified and normalized to actin. Immunohistochemical staining for MYD88 was performed in a different cohort of 12 patients with rosacea and 12 controls, and positively-staining cells were counted across five consecutive 40x fields. Statistical analyses compared the differences between the two groups via a dedicated software package. Results: On western blotting, the mean ratios of MYD88 to actin were 13.8 (standard deviation = 14.1) and 44.3 (standard deviation = 39.6) in control and rosacea patients, respectively ( p = .002). On immunohistochemistry, the mean numbers of positively-staining cells were 12.1/40x field (standard deviation = 9.61/40x field) and 27.4/40x (standard deviation = 18.7/40x field) in control and rosacea patients, respectively ( p = .0438). Conclusions: MYD88 is enriched in eyelid specimens of rosacea. This finding further implicates the innate immune system in the pathogenesis of rosacea, and is consistent with previous reports regarding the role of this protein in ocular surface disease and the previously-implicated cellular features of the disease. Inhibition of MYD88 may be a successful treatment strategy to manage rosacea.